Can we use structural lesions seen on MRI of the sacroiliac joints reliably for the classification of patients according to the ASAS axial spondyloarthritis criteria? Data from the DESIR cohort. Issue 2 (4th August 2016) - Bakker, Pauline A C; van den Berg, Rosaline; Lenczner, Gregory; Thévenin, Fabrice; Reijnierse, Monique; Claudepierre, Pascal; Wendling, Daniel; Dougados, Maxime; van der Heijde, Désirée
Abstract : Objectives: Investigating the utility of adding structural lesions seen on MRI of the sacroiliac joints to the imaging criterion of the Assessment of SpondyloArthritis (ASAS) axial SpondyloArthritis (axSpA) criteria and the utility of replacement of radiographic sacroiliitis by structural lesions on MRI. Methods: Two well-calibrated readers scored MRI STIR (inflammation, MRI-SI), MRI T1-w images (structural lesions, MRI-SI-s) and radiographs of the sacroiliac joints (X-SI) of patients in the DEvenir des Spondyloarthrites Indifférenciées Récentes cohort (inflammatory back pain: ≥3 months, <3 years, age <50). A third reader adjudicated MRI-SI and X-SI discrepancies. Previously proposed cut-offs for a positive MRI-SI-s were used (based on <5% prevalence among no-SpA patients): erosions (E) ≥3, fatty lesions (FL) ≥3, E/FL ≥5. Patients were classified according to the ASAS axSpA criteria using the various definitions of MRI-SI-s. Results: Of the 582 patients included in this analysis, 418 fulfilled the ASAS axSpA criteria, of which 127 patients were modified New York (mNY) positive and 134 and 75 were MRI-SI-s positive (E/FL≥5) for readers 1 and 2, respectively. Agreement between mNY and MRI-SI-s (E/FL≥5) was moderate (reader 1: κ: 0.39; reader 2: κ: 0.44). Using the E/FL≥5 cut-off instead of mNY classification did not change in 478 (82.1%) and 469 (80.6%) patients for readers 1 and 2, respectively. Twelve (reader 1) or ten (reader 2) patients would not be classified as axSpA if only MRI-SI-s was performed (in the scenario of replacement of mNY), while three (reader 1) or six (reader 2) patients would be additionally classified as axSpA in both scenarios (replacement of mNY and addition of MRI-SI-s). Similar results were seen for the other cut-offs (E≥3, FL≥3). Conclusions: Structural lesions on MRI can be used reliably either as an addition to or as a substitute for radiographs in the ASAS axSpA classification of patients in our cohort of patients with short symptom duration.